Strategies In Fostering Student's Autonomy At The First Year In SMK Sahid Surakarta - Irawan, Ita (2012)
This research aims to describe the strategies implemented by the teacher of SMK Sahid Surakarta in fostering student's autonomy in the first year. The result of this study hopefully will give contribution to English teachers especially in fostering student's autonomy. This research studies the strategies in fostering student's autonomy in students of SMK Sahid Surakarta at 1H3. The type of this research is micro ethnography research which aims at describing and writes the habit or acts the people in one place. The subjects of this research are the students and the teachers of SMK Sahid Surakarta. The methods of collecting data are interviewing, observing, and documentation. The data are taken from the subjects of the research analyzing. The result of this research shows that the teacher of SMK Sahid Surakarta used almost all of strategies in fostering student's autonomy proposed by Cotterall and Chan. The result are the English teacher in SMK Sahid Surakarta implemented some strategies to make the students autonomous namely distributing different topic for each student, questioning and answering, giving tasks and exercises, finding the material for the next meeting, grouping, checking materials, class dialogue. The second is problem faced by the teacher. Second, there are six problems faced by the teacher in the class: student's dependence, difficulties on the materials, student's unconfidence, difficulties to handle the student, difficulties in explaining the material, and indiscipline the student. The last is the strengths and weaknesses of those strategies in fostering student's autonomy. In general the strengths and weaknesses of those strategies are: the strengths are the student has brave and willing to show their own idea in front of class, then the student has willing to revise the material which not correct. The weaknesses are some of the students feel nervous and passive in the class.